Collateral augmentation treatment with a combination of acetazolamide and head-down tilt in a rat ischemic stroke model. (March 2020) - Han, Minho; Kwon, Il; Ha, Jimin; Kim, Jayoung; Cha, Myoung-Jin; Kim, Young Dae; Heo, Ji Hoe; Nam, Hyo Suk
Highlights: We explored the effectiveness of ACZ, HDT, and ACZ + HDT in the transient MCAO. Collateral augmentation treatments showed better outcomes after transient MCAO. ACZ + HDT improved neurological scores and reduced brain water content. Abstract: Cerebral collaterals is crucially important in the pathophysiology of acute ischemic stroke and associated with outcome after reperfusion therapy. We explored the effectiveness of collateral augmentation treatment with a combination of acetazolamide (ACZ) and head-down tilt (HDT) in the transient middle cerebral artery occlusion (MCAO) rat model. Transient MCAO was induced in all animals for 1.5 h, followed by reperfusion for 22.5 h. Seventy-two male Wistar rats were divided into four treatment groups: control, ACZ, HDT, and combination. Twenty sham rats, which underwent surgery, were randomly allocated to these groups. Twenty-four hours after MCAO or sham surgery, we measured the infarction volume, brain edema (aquaporin-4 [AQP4], and brain water content), and neurological deficits (Garcia and Longa tests). Collateral augmentation treatments were associated with reduced infarction volume, less brain edema, and better neurological outcomes compared with untreated animals. More specifically, ACZ and HDT treatments resulted in small infarction volumes, and HDT was associated with a low AQP4 expression and improved neurological score, while the combination of ACZ and HDT improved neurological scores and reduced brain water content. This study shows that collateral augmentation treatments are associated with a better stroke prognosis compared with untreated animals after transient MCAO. The combination of ACZ and HDT seems to have some synergistic effect, but was not proven to be superior to HDT treatment alone.